Learning Evaluation for Elementary, Middle, and High School Levels - Rahayu, Ayu Puji; Saepurrohman, Saepurrohman; Junaedi, Jujun; Sonari, Heny (Indonesian Journal of Community Empowerment (IJCE), 2023)
At the elementary, secondary, and higher education levels, there are significant differences in the evaluation approaches required. In elementary schools, the evaluation approach typically focuses more on formative assessment to provide constructive feedback, thereby increasing student engagement and motivation to learn. This method is designed to provide educators with the skills and knowledge necessary to implement effective and relevant learning evaluations. This community service program significantly contributes to the understanding and practice of learning evaluation at the elementary, secondary, and higher education levels. With continued support in technology and innovative methods, it is hoped that the results will transform the culture of evaluation in schools and improve the overall quality of education. With increased evaluation knowledge and skills among educators, it is hoped that the overall quality of education will improve.